Hemophagocytic lymphohistiocytosis associated with hepatosplenic T-cell lymphoma: case report - Vitor Ribeiro Paes; Patrícia Picciarelli de Lima; Sheila Aparecida Coelho Siqueira (University of São Paulo, 2014)
Hepatosplenic T-cell lymphoma (HSTCL) is a rare non-Hodgkin lymphoma, marked by liver, spleen, and bone marrow sinusoidal infiltration, with an aggressive clinical course, which represents a difficult diagnostic task for clinicians and pathologists. Another equally severe and challenging condition is the hemophagocytic lymphohistiocytosis (also called hemophagocytic syndrome [HS]), which is often associated with hematologic malignancies and infectious diseases. The authors report the case of a 56-year-old woman diagnosed with HSTCL based on bone marrow aspirate flow cytometry and skin biopsy. The patient underwent a cycle of chemotherapy but the outcome was unfavorable with multiple organ failure. The laboratory analysis was consistent with HS. The autopsy confirmed both the remaining lymphoma in the pulmonary vessels and the hemophagocytic cells in the spleen and bone marrow.